Moisturizers for Acne: What are their Constituents? - Chularojanamontri, Leena (Matrix Medical Communications, 2014)
Acne is a chronic inflammatory disease of the pilosebaceous unit that affects almost all teenagers. Different treatments offer different modes of action, but aim to target acne pathology. Topical therapies, such as benzoyl peroxide, retinoids, antibiotics with alcohol-based preparations, and salicylic acid, can cause skin irritation resulting in a lack of patient adherence. Some physicians recommend patients use moisturizers as adjunctive treatment of acne, especially when either topical benzoyl peroxide or a retinoid is prescribed. Furthermore, some evidence shows that moisturizers can contribute independently to improve signs and symptoms of acne. Moisturizers contain three main properties, which are occlusive, humectant, and emollient effects. Currently, many moisturizers claim to be suitable for acne treatment. This article aims to provide a review of the active ingredients and properties of those moisturizers. Fifty-two moisturizers for acne were included for analysis. Most of the products (92%) have anti-inflammatory properties apart from occlusive, humectant, and emollient effects. Anti-acne medications, including salicylic acid, benzoyl peroxide, and retinol, were found respectively in 35, 10, and 8 percent of the moisturizer products containing anti-inflammatory properties. More than half of the products contain dimethicone and/or glycerin for its moisturizer property. Aloe vera and witch hazel are botanical anti-inflammatories that were commonly found in this study. Scientific data regarding some ingredients are discussed to provide a guide for physicians in selecting moisturizers for acne patients.